2008
DOI: 10.2174/1874924000801010038
|View full text |Cite
|
Sign up to set email alerts
|

Private Pediatric Clinic Characteristics Associated with Influenza Immunization Efforts in the State of Georgia: A Pilot Evaluation

Abstract: The Advisory Committee on Immunization Practices (ACIP) recently recommended that all children 6 months to 18 years be vaccinated annually against influenza. Because pediatricians will be critical for implementing this recommendation, we assessed the characteristics of immunization providers associated with the greatest efforts to vaccinate children against influenza. Using a cross-sectional survey of 35 private pediatric clinics in Georgia, we found that adding extra hours for immunization during the influenz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Pilot interventions including both women and men led to NIMH- and National Institute of Child Health and Human Development (NICHD)-supported larger scale studies in Zambia and USA with couples [811, 1316, 20, 21]. The findings from these couple studies confirmed the desirability of working with both partners concurrently, albeit separately, in gender concordant groups, and a pilot translation to a community health center was successfully conducted [12]. A funded application to NICHD to translate the intervention into the community through six CHCs in Zambia led to extensive groundwork to optimize the introduction and uptake of the program, including criteria for the selection of CHCs, clinic staff sensitization and “buy in,” and support from the Ministerial and Provincial Health Department leadership to the local community advisory boards (CABs) at each community health center.…”
mentioning
confidence: 99%
“…Pilot interventions including both women and men led to NIMH- and National Institute of Child Health and Human Development (NICHD)-supported larger scale studies in Zambia and USA with couples [811, 1316, 20, 21]. The findings from these couple studies confirmed the desirability of working with both partners concurrently, albeit separately, in gender concordant groups, and a pilot translation to a community health center was successfully conducted [12]. A funded application to NICHD to translate the intervention into the community through six CHCs in Zambia led to extensive groundwork to optimize the introduction and uptake of the program, including criteria for the selection of CHCs, clinic staff sensitization and “buy in,” and support from the Ministerial and Provincial Health Department leadership to the local community advisory boards (CABs) at each community health center.…”
mentioning
confidence: 99%